Implementasi Pendidikan Karakter Holistik untuk Penguatan Nilai Empati dan Tanggung Jawab Anak Sekolah Dasar - Ulzana, Yuhanita; Restian, Arina; Dwi Astuti, Rina; Alhudayatul Ustadza, Cebeng (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to describe the implementation of holistic character education in developing empathy and responsibility values among elementary school students through reflective and contextual learning approaches. The research method used is descriptive qualitative with a case study design, involving participatory observation, semi-structured interviews, and document analysis to gain a comprehensive understanding of the learning process dynamics. The findings indicate that reflective learning strategies such as journaling, group discussions, and role-playing effectively encourage students to express emotions, understand others' perspectives, and engage in deep moral reflection. Meanwhile, the contextual learning approach linked to real-life situations, such as social projects and community service, helps students apply responsibility concretely in their daily lives. The collected data show a significant increase in indicators of empathy, reflective ability, and responsibility following the implementation of the holistic character education model. These findings affirm that integrating cognitive, affective, and moral behavioral dimensions through authentic experiences can strengthen the overall character development of students. The practical implications of this study can serve as a reference for educators and school institutions in designing humanistic and meaningful learning models. Keyword: character education; reflective approach; contextual approach; empathy; responsibility